Transformasi Pernikahan Siri ke Resmi: Impilikasi Hukum, Status Anak, dan Legitimasi di Mata Negara (Studi Kasus KUA Kecamatan Mamajang) - Ramadhani, Elsa Dwi Aryana; Aziz, Khalid Abd; Faridh, Mifta Ghulam; Ikhsan, Muhammad; Hidayah, Nur; Qurrahman, Muh. Taufiq; Ardah, Lukman; Ishak, Nurfaika (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Unregistered marriage (nikah siri), which is conducted without official registration at the Office of Religious Affairs (Kantor Urusan Agama or KUA), is often chosen by couples for various reasons, such as administrative constraints, economic factors, or cultural and religious considerations. However, this type of marriage has significant legal implications, particularly concerning the legal status of the wife and children born from the marriage. Children born from an unregistered marriage are only legally recognized as having a civil relationship with their mother and maternal family, as stipulated in Article 43(1) of Law No. 1 of 1974 on Marriage, which was later reinforced by Constitutional Court Decision No. 46/PUU-VIII/2010. To address these legal issues, couples can file for isbat nikah (marriage validation) at the Religious Court as a step toward legalizing their marriage. Once isbat nikah is granted, the marriage can be officially registered at the KUA, thereby providing legal protection for the wife and children and ensuring state recognition of the marriage. This process not only formalizes the family’s legal status but also guarantees the fulfillment of children’s civil rights, such as inheritance rights, legal identity, and social protection. This study aims to analyze the dynamics of transitioning from nikah siri to officially registered marriage, the underlying factors, and the legal implications for children’s status and marriage legitimacy in the eyes of the state.